The Power Savings Possibilities by Light in the Smart Home Care (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
When designing a visualisation environment for controlling the building service system in Smart Home Care in order to meet the needs of seniors, emphasis is placed not only on the ease of operation and safety of the elderly, but also on possible cost savings in the operation of the Smart Home Care system. The article describes a study design of potential savings of electrical energy using software developed for the efficient control of lighting to a constant level with the KNX bus system or with the use of the wireless xComfort system.